Research on rigger equipment for retrieving vehicles from lake depths (Mongolian Journal of Agricultural Sciences, 2025)
This study contributes to ongoing efforts to protect the ecosystem of Lake Khuvsgul by supporting the remediation of hazardous waste and the reduction of pollution within the lake. A key focus of the operation is the analysis and selection of rigger equipment used in the retrieval of sunken vehicles and machinery from significant depths. In 2023–2024, a total of 11 submerged vehicles and machines were successfully recovered from depths ranging from 33 to 171 meters, including a motorboat, a ZIL-130 truck with trailer, a UAZ-469, a TT-4 tracked mountain tractor, and a YAG-6 truck. The retrieval technology was implemented through four sequential stages: preliminary pulling to free the objects from sediment, deep-water lifting, transportation toward the lakeshore, and final extraction onto land. This article presents the engineering calculations, equipment selection, and practical application of rigger systems utilized at each stage, offering insights to support future environmental recovery operations in deep freshwater ecosystems.